Non-destructive method for extracting DNA from cowpea seeds - Victoria de Oliveira Santos; Eveline Nogueira Lima; Ingrid Bernardo de Lima Coutinho; Cândida Hermínia Campos de Magalhães; Patricia do Nascimento Bordallo (Pesquisa Agropecuária Tropical)
Studies employing molecular markers require DNA extraction. For cowpea, DNA extraction is typically performed on young leaf tissue; however, this procedure requires significant time, space and resources. This study aimed to establish a protocol for extracting DNA from scarified cowpea seeds while preserving the embryo viability. Three DNA extraction protocols were evaluated to determine the most suitable non-destructive method: the CTAB method, the NaOH-Tris method and a commercial kit. The commercial kit produced DNA of higher purity, when compared to the other protocols. Nevertheless, the amplified products from the commercial kit and the CTAB protocol were highly similar. Five genetic similarity groups were identified. No significant differences were observed for the germination rate or the emergence speed of scarified seeds. The genetic variability assessment validated the efficiency of the proposed methodology. This protocol effectively preserved the embryo viability, enabling the subsequent use of the seeds in genetic breeding programs.